Предмет: Математика,
автор: fghghng
-4(х-2)=-6
3(х-5)=х+3
Ответы
Автор ответа:
0
-4(х-2)=-6
-4х+8=-6
-4х=-6-8
-4х=-14
х=14/4
х=7/2
3(х-5)=х+3
3х-15=х+3
3х-х=3+15
2х=18
х=9
-4х+8=-6
-4х=-6-8
-4х=-14
х=14/4
х=7/2
3(х-5)=х+3
3х-15=х+3
3х-х=3+15
2х=18
х=9
Автор ответа:
0
1) x=6÷4=1,5
x=1,5+2=3,5
2) 3x-15=x+3
3x-x=3+15
2x=18
x=9
x=1,5+2=3,5
2) 3x-15=x+3
3x-x=3+15
2x=18
x=9
Похожие вопросы
Предмет: Математика,
автор: mouseorphan
Предмет: Математика,
автор: Nytelka228
Предмет: Литература,
автор: pohnovskaya
Предмет: Математика,
автор: tkachevavalent
Предмет: Физика,
автор: нггг